AJAMODA (APIUM LEPTOPHYLUM)- A NATURAL PAINKILLER - singh, *Ritu; Singh, D.C.; Tomar, Pravesh; Verma, Sarita (International Journal of Ayurveda and Pharma Research, 2016)
Ajamoda is an important drug of Ayurveda, Siddha and Unani systems of medicine, which consists of umbelliferous fruits. The drug to be used in the formulations are fruits of Apium leptophyllum. Apium is a genus of about 20 species of flowering plants in the family Apiaceae. Some species are edible, notably Apium graveolance, Apium leptophylum, which includes the commercially important vegetables celery, celeriac and chinese celery. It is grown extensively in the South Asia, Southeast Asia, and Indonesia. Its aromatic dried fruits, like its close relative ajwain, are often used in Bengali cuisine but are rarely used in the rest of India. The fresh leaves are used as an herb in Thailand and it is used medicinally in Myanmar. The small dried fruits, commonly referred to as seeds, are similar in appearance to those of ajwain, celery, and caraway. Because of their similarity in both appearance and flavor, it is often confused or substituted with celery seed. Ajamoda consists of dried, aromatic fruits of Apium leptophyllum (Pers.) F. V. M. ex Benth. (Fam. Umbelliferae); an annual herb cultivated in Andhra Pradesh, Gujarat, Madhya Pradesh and Karnataka; collected by thrashing plants on a mat and dried in shade or in drying sheds. The oil of seeds of Ajamoda is also used in compounding Ayurvedic formulations. While, fatty oil of seeds is antispasmodic and nerve stimulant, seeds of celery are rich in vitamin-B.